OPTIMIZATION OF ROOT TRAINER COCOPEAT PLANTING MEDIA THROUGH ZEOLITE AND HUMIC ACID APPLICATION ON RUBBER NURSERY - Stevanus, Charlos Togi; Cahyo, Andi Nur (Jurnal Penelitian Karet, 2020)
Cocopeat as root trainer?s planting media has low nutrition content. This research aimed to determine the effect of various zeolit and humic acid dose on the growth and nutrition uptake of rubber planting material. This research was conducted in Sembawa Research Centre Nursery on April 2018 to January 2019 using IRR 112 rubber clone. This research was arranged in completely randomized design (CRD) with two factors and three replicates. The first factor was zeolit dose that consisted of four levels, namely 0; 7.5; 15; and 22.5 gram/plant. The second level was humic acid dose, that consisted of four levels, namely 0; 7.5; 15; and 22.5 ml/l water. Zeolite and humic acid significantly improved lateral root and leaves biomass respectively. Furthermore, zeolite also significantly improved lateral root?s N and P uptake as well as leaves? N. In addition humic acid improved leaves? P and K uptake as well as stem?s N uptake. The optimal application dose was 7.5 gram/plant for zeolite and 7.5 ml/l water for humic acid.